Successful Conservative Treatment of a Cesarean Scar Pregnancy with Systemically Administered Methotrexate and Subsequent Dilatation and Curettage: A Case Report - Anis Fadhlaoui; Mohamed Khrouf; Khaled Khémiri; Kais Nouira; Anis Chaker; Fethi Zhioua (Case Reports in Obstetrics and Gynecology)
Cesarean scar pregnancy is a rare type of ectopic pregnancy associated with severe complications such as uterine rupture, uncontrollable bleeding which may lead to hysterectomy, and definitive infertility. Many therapeutic options are available such as Dilatation & Curetage, excision of trophoblastic tissues using either laparotomy or laparoscopy, systemically administered Methotrexate, and more recently uterine artery embolization. The use of Methotrexate sometimes required laparotomy later because of severe hemorrhage. Through this paper, we demonstrated that viable cesarean scar pregnancy can be managed safely by systemically delivered Methotrexate at the cost of a prolonged followup.